Biomechanical comparison between cortical screw-rod construct versus pedicle screw-rod construct in transforaminal lumbar interbody fusion - Chan, C.Y.W.; Sem, S.W.; Bashir, E.S.; Saw, L.B.; Shanmugam, R.; Kwan, M.K. (SAGE Publications (UK and US), 2017)
OBJECTIVE: To compare construct stiffness of cortical screw (CS)-rod transforaminal lumbar interbody fusion (TLIF) construct (G2) versus pedicle screw (PS)-rod TLIF construct (G1) in the standardized porcine lumbar spine.